2023
DOI: 10.1108/ijbpa-05-2022-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cement and geopolymer stabilization on the thermal comfort: case study of an earthen building in Burkina Faso

Abstract: PurposeThe stabilization of earthen blocks improves their mechanical strength and avoids adobe construction erosion due to rainwater. However, the stabilization affects the thermal properties of the earthen blocks, and thus their capacity to provide adequate thermal comfort to occupants. This article examines the influence of cement and geopolymer binders on thermal comfort in compressed earthen buildings in hot and arid climates.Design/methodology/approachThe test cell is on the building platform in Burkina F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, the country faces a hot and dry climate with maximum temperatures of nearly 40˚C in 2015 [2] and remains constantly growing [3]. It then becomes essential to be able to offer local residents affordable, healthy and thermally comfortable housing, and adapted to increasingly severe climatic conditions [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the country faces a hot and dry climate with maximum temperatures of nearly 40˚C in 2015 [2] and remains constantly growing [3]. It then becomes essential to be able to offer local residents affordable, healthy and thermally comfortable housing, and adapted to increasingly severe climatic conditions [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the energy and ecological issues linked to this material are pushing the search for new alternatives. In fact, 4 billion tons of cement are produced worldwide with an annual growth of 4% [4]. This intensive production would be responsible for emissions of 45.45 billion tons of CO 2 globally in scenario 3 of shared socio-economic pathways [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern construction uses materials such as cement and steel which are not always adapted to the hot and dry climatic conditions of many regions such as Burkina Faso. This increases the thermal discomfort of non-air-conditioned buildings and the electricity consumption due to the use of mechanical air conditioning systems for thermal comfort [2,[8][9][10]. Studies have shown that the analytical model for calculating the PMV index predicts a good thermal sensation in mechanically conditioned buildings; but it unfortunately predicts a warmer thermal sensation than that of felt by the occupants in buildings with natural ventilation [11].…”
Section: Introduction Context Of the Studymentioning
confidence: 99%